NIKAH LINTAS AGAMA PERSPEKTIF HUKUM ISLAM - Syam, Aydi (DIKTUM: Jurnal Syariah dan Hukum, 2015)
Focus of this paper is to study the legality of Islamic law on interfaith marriage . Basing on some proposition naqliy understood that there are two laws that are contradictory, that is: absolutely forbidden marriage and marriage is permitted / allowed conditionally. This conclusion is based on the QS. al-Baqarah (2) : 221 ; QS. al-Mumtahanah (60) : 10 ; and QS. al-Maâ€™idah (5) : 5. While understanding the argument of the methodology used is the type of pattern bayÄniy mauÄ‘Å«â€™iy, tahlÄ«liy, and muqÄran. While the multidisciplinary approach is more focused on the study of semiotics, historical and culture analysis.